Using Correlation to Explore the Impact of Corona Virus Disease on Socioeconomics - Fitriadi Fitriadi; Jiuhardi Jiuhardi; Arfiah Busari; Yana Ulfah; Y. Permadi Hakim; Erwin Kurniawan A.; Dio Caisar Darma (Emerging Science Journal, 2022)
In the 21stcentury, the tragedy of the pandemic shocks the world. This non-natural disaster is called COVID-19. Its dominant effect is also worrying about social and economic conflicts at local, national, and even international levels. The orientation of this research is to investigate the impact of COVID-19 on the socioeconomic aspects in Indonesia from 2020-2022. We set the research using official/secondary publications. Data analysis was interpreted in three formats: Pearson, Kendall's, and Spearman's correlations. It channelled empirical testing through Microsoft Excel and SPSS v.25. Social items include migration, mortality, domestic violence, and sexual harassment, while the nine economic items are per capita spending, well-being, unemployment, poverty, and labor productivity. Then, statistical instruments were reviewed based on the correlation coefficient and level of significance (5% for Pearson and 1% for Kendall's and Spearman's). The results are not much different between Pearson's approach, Kendall's and Spearman's. In Pearson model, it proved a negative correlation when COVID-19 increases, so migration, unemployment, poverty, and labor productivity decrease. COVID-19 has had a positive impact on mortality, domestic violence, sexual harassment, per capita spending, and well-being. In Kendall's and Spearman's tests, poverty and labor productivity have actually increased because of COVID-19. Implementing semi-lockdown is a priority so that the social and macroeconomic constellations continue without ignoring the latent dangers of COVID-19. The limitations of the study are discussed in the future. Doi: 10.28991/esj-2022-SPER-012 Full Text: PDF